LEARNING ASSISTANCE FOR EARLY CHILDREN IN MARANG, TANGO MOLAS VILLAGE, LAMBA LEDA TIMUR DISTRICT (LP3K Lampung, 2022)
Marang is located in Tango Mola's village, East Lamba Leda sub-district. This village has quite a lot of children. However, education for early childhood has not occurred in this village. Therefore, the PKM team carries out early childhood learning assistance. This assistance was carried out for 20 children in Marang village. This activity aims to increase independence, self-confidence, and responsibility in children. To solve the problems in Marang, the PKM team has a solution that is carried out through several methods: observation and interviews, planning, mentoring, and evaluation. Based on the results of data analysis, it was found that 80% of children have good independence, 85% of children have good self-confidence, and 60% of children are well responsible.